2013
DOI: 10.1002/jcph.96
|View full text |Cite
|
Sign up to set email alerts
|

RadixPuerariae: An overview of Its Chemistry, Pharmacology, Pharmacokinetics, and Clinical Use

Abstract: Radix Puerariae has been traditionally used for the treatment of diarrhea, acute dysentery, deafness and cardiovascular diseases. Yege (Gegen or Radix Puerariae lobatae), the dried root of Pueraria lobata (Wild.) Ohwi, has been widely used in China and, to a lesser extent, in Japan, Korea, and the United States. Although they have been classified into different categories in Chinese Pharmacopoeia, Yege is often used interchangeably in practice with Fenge (Radix Puerariae thomsonii), which is the dried root of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
130
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(135 citation statements)
references
References 71 publications
(77 reference statements)
1
130
0
2
Order By: Relevance
“…The second aim of this work was to evaluate if the HDM-PAMPA kept its predictive power when applied to the study of constituents directly in crude plants extracts. The plant is used as a general medicine for improving body functions but also more specifically in the treatment of diarrhea, acute dysentery, deafness, or cardiovascular diseases [35]. For each of these selected medicinal plants, a crude plant extract containing the metabolites that are ingested when the medicinal plant is orally taken was prepared.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The second aim of this work was to evaluate if the HDM-PAMPA kept its predictive power when applied to the study of constituents directly in crude plants extracts. The plant is used as a general medicine for improving body functions but also more specifically in the treatment of diarrhea, acute dysentery, deafness, or cardiovascular diseases [35]. For each of these selected medicinal plants, a crude plant extract containing the metabolites that are ingested when the medicinal plant is orally taken was prepared.…”
mentioning
confidence: 99%
“…The extracts were prepared in order to insure that they contain the metabolites that are ingested when the medicinal plant is orally taken: a methanolic extract of the fruits from A. archangelica mostly composed of furanocoumarins [43,44], a decoction of aerial parts of W. indica containing quinoline alkaloids [33], and a decoction of roots of P. montana var. lobata with flavonoid glycosides [35]. The HDM-PAMPA method used for pure NPs was adapted to the analysis of crude plant extracts by simply increasing the amount of sample (crude extract) initially loaded in the donor compartment since single metabolites are found at lower concentrations in mixtures.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A WHO több mint száz betegséget sorol fel, amelyekben az akupunktúra hatásosságára hatásvizsgálatok utalnak [4]. A kínai orvoslásban használt szerekből többet átvett már a modern tudomány (ginkgo biloba [5], artemisia annua [6], pueraria lobata [7] stb). A kínai akupunktúra szerepel az UNESCO szellemi világöröksé-gek listáján [8].…”
Section: A Hagyományos Kínai Orvoslásunclassified
“…Therefore, it's believed to exhibit beneficial effect on bone tissue by mimicking the biological responses of estrogens. 5,6) Previously, we reported that Puerarin could suppress bone resorption and promote bone formation in vitro, but the former effect was stronger than the latter. 7) However, Zhang et al 8) and Tiyasatkulkovit et al 9) observed strong promotion effects of puerarin on bone formation.…”
mentioning
confidence: 99%